Laskar Jihad : Islam, Militancy, and the Quest for Identity in Post-New Order Indonesia - Hasan, Noorhaidi (Book collections on Project MUSE., 2006)
An in-depth study of the militant Islamic Laskar Jihad movement and its links to international Muslim networks and ideological debates. This analysis is grounded in extensive research and interviews with Salafi leaders and activists who supported jihad throughout the Moluccas.